Top-down and bottom-up deficits in conflict adaptation after frontal lobe damage. - Funes, M; Lupiáñez, J; Humphreys, G (2010)
The ability to adaptively control our responses to conflicting information is crucial if we are to respond in a flexible manner to the environment. The "conflict monitoring model" proposes that the prefrontal cortex is responsible of reactive adjustments in cognitive control. We present neuropsychological data contrasting the performance of patients with prefrontal lesions with the one exhibited by patients with lesions outside the frontal lobe and nonlesioned participants, on the processes involved in the dynamic adaptation to conflicting stimulus information. Relative to both lesioned and nonlesioned control groups, prefrontal patients were impaired in adapting to conflict when all features of the conflicting stimuli and their associated responses changed on consecutive trials. However, the prefrontal patients also showed an unusually large conflict adaptation effect when the stimuli and/or response features repeated across trials. We conclude that prefrontal cortex is relevant both for genuine "top-down" conflict monitoring and for regulating the influence of "bottom-up" responses based on the integration of stimulus features across trials.